Nursing competence in municipal in-patient acute care in Norway: a cross-sectional study - Torunn Kitty Vatnøy; Marianne Sundlisæter Skinner; Tor-Ivar Karlsen; Bjørg Dale (BMC, 2020)
Abstract Background The primary health care services are becoming increasingly complex, which presents challenges for the municipal nursing services. In Norway, municipal in-patient acute care (MipAC) has been introduced in all municipalities, and the competence at the services has been questioned. Few studies have examined the nursing services in the units. This study aims to get an overview of the nursing competence in those units across geographical regions, and different groups of organisation and localisation. Methods A cross-sectional study was conducted, and an ad hoc questionnaire was distributed to first-line leaders in all the MipAC units in Norway. Data were collected in the period between 6 March 2019 to 6 June 2019. Measures to get an overview of the nursing competence were ratio of registered nurses (RNs) in staff, count of shifts with only one RN on duty and count of RNs with master's degrees/specialisation. Descriptive comparative statistics were used. Results Of all 226 first-line leaders invited to participate, 207 (91.6%) responded to the questionnaire. Overall a considerable variance across the sample was revealed. The median ratio of RNs in staff was 56 (IQR = 40-70), the count of shifts with only one RN on duty median 28 (IQR = 5-49), and the count of RNs with a master's degree or specialisation median 3 (IQR = 0-5). The regions of Northern and Central Norway, MipACs located in nursing home and MipACs organised at long-term care units, showed significantly lower nursing competence in staff compared to the remaining institution and organisations. Conclusion This study generates knowledge that can inform planning, priorities and interventions that may be initiated at all organisational and political levels concerning the MipAC services. An overall conclusion is that advanced nursing competence is lacking. The study also highlights the most urgent direction for improvements regarding nursing competence in the services. It seemed to be MipACs in Northern and Central Norway, and those located at nursing homes organised together with long-term care units, that needed improvements the most.